De band die tijd en afstand overbrugt - Kimura, Teirō; Dam, Ellen van (Zeist De Hofreis, 2014)
Teirō Kimura, former superintendent of education in Yamada, was partly behind the bond of friendship between Zeist and Yamada. He has written a book on the history of contacts between Yamada and the Netherlands since 1643, when the VOC ship the Breskens sailed into Yamada bay, and on the contacts and friendship ties with Zeist in particular since 1993.
Keywords: History; Japan; Netherlands